Wanamaker's temple : the business of religion in an iconic department store - Kirk, Nicole C. (New York University Press, 2018)
"On Christmas Eve, 1911, John Wanamaker stood in the middle of his elaborately decorated department store building in Philadelphia as shoppers milled around him picking up last minute Christmas presents. On that night, as for years to come, the store was filled with the sound of Christmas carols sung by thousands of shoppers, accompanied by the store's Great Organ. Wanamaker recalled that moment in his diary, 'I said to myself that I was in a temple, ' a sentiment quite possibly shared by the thousands who thronged the store that night. Remembered for his store's extravagant holiday decorations and displays, Wanamaker built one of the largest retailing businesses in the world and helped to define the American retail shopping experience. From the freedom to browse without purchase and the institution of one price for all customers to generous return policies, he helped to implement retailing conventions that continue to define American retail to this day. Wanamaker was also a leading Christian leader, participating in the major Protestant moral reform movements from his youth until his death in 1922. But most notably, he found ways to bring his religious commitments into the life of his store. He focused on the religious and moral development of his employees, developing training programs and summer camps to build their character, while among his clientele he sought to cultivate a Christian morality through decorum and taste. Wanamaker's temple examines how and why Wanamaker blended business and religion in his Philadelphia store, offering a historical exploration of the relationships between religion, commerce, and urban life in the late nineteenth and early twentieth century and illuminating how they merged in unexpected and public ways. Wanamaker's marriage of religion and retail had a pivotal role in the way American Protestantism was expressed and shaped in American life, and opened a new door for the intertwining of personal values with public commerce"--Publisher's website